The Preliminary Study of Utilization of Water Chestnut as Supercapacitor Electrode Using Steam Activation - Zulkifli Zulkifli; Awitdrus Awitdrus; Erman Taer (PSI-Aceh, 2018)
Purun tikus (eleocharis dulcis) merupakan tumbuhan gulma yang bersifat polutan di perairan tawar. Efek pertumbuhan purun tikus yang cepat menyebabkan pendangkalan perairan, gangguan sistem irigasi dan pengurangan oksigen bawah air. Salah satu upaya pemanfaatan purun tikus yang bernilai tambah tinggi adalah purun tikus sebagai elektroda karbon superkapasitor. Karbon aktif berasaskan purun tikus dibuat dengan metode dua langkah secara simultan yaitu karbonisasi pada suhu 600°C dalam lingkungan nitrogen dan aktivasi fisika menggunakan uap air pada suhu 900°C selama 1 jam. Densitas karbon aktif menurun dari 0,85 menjadi 0,78 gr/cm3 setelah diaktivasi. Sifat elektrokimia elektroda karbon diukur dengan metode siklik voltammetri. Kapasitansi spesifik elektroda karbon masing-masing 58, 33 dan 23 F/g pada laju imbasan 1, 2 dan 5 mV/s. Hasil penelitian ini menunjukkan bahwa purun tikus dapat dijadikan elektroda superkapasitor dan menjadi solusi untuk mengurangi kerusakan ekosistem perairan tawar. Water chestnut are polluted weed plant in fresh water. The effect of rapid growth of water chestnut causes siltation of water, irigation system disturbance and reduction of oxygen underwater. One of the effort of the value added utilization of water chestnut is as carbon electrode for supercapacitor application. Water chestnut based activated carbon is prepared by a two-step method simultaneously i.e. carbonization at 600°C in a nitrogen atmospheric and physical activation using steam at 900 °C for a hour. The density of activated carbon after activation is decreased from 0,85 to 0,78 gr/cm3. The electrochemical properties of the carbon electrode are measured using cyclic voltammetry method. The specific capacitance of carbon electrode are 59, 33 and 23 F/g at the scan rate of 1, 2 and 5 mV/s, respectively. The result of this study are indicated that water chestnut suitable for supercapacitor electrode and become a solution to reduce the freshwater ecosystem damage. Keywords: Purun tikus, superkapasitor, siklis voltammetri, kapasitansi spesifik, perairanREFERENCEAsikin, S. dan Thamrin, M. 2012. Manfaat Purun Tikus (Eleocharis Dulcis) Pada Ekosistem Sawah Rawa. Jurnal Litbang Pertanian, 31(1): 35-42Arepalli, S., Fireman, H., Huffman, C., Moloney, P., Nikolaev, P., Yowell, L., Higgins, C. D., Kim, K., Kohl, P. A., Turano, S. P. and Ready W. J. 2005. Carbon-nanotube-based electrochemical double-layer capacitor technologies for spaceflight applications. Journal of The Minerals, Metals and Materials Society, 57:26-31.Erari, S.S., Mangimbulude, J., Lewerissa, K. 2012. Pencemaran Organik di Perairan Pesisir Pantai Teluk Youtefa Kota Jayapura, Papua. Prosiding Seminar Nasional Kimia Unesa. ISBN 978-979-028-550-7. (C): 327-340.Farma, R., Deraman, M., Awitdrus, A., Talib, I.A. Taer, E., Basri, N.H., Manjunatha, J.G., Ishak, M.M., Dollah, B.N.M., Hashmi, S.A. 2013. Preparation of highly porous binderless activated carbon electrodes from fibres of oil palm empty fruit bunches for application in supercapacitors. Bioresource Technology. 132:254–261Feng, C.W., R.L. Tseng., C.C. Hu., C.C Wang., 2015, Effects of pore structure and electrolyte on the capasitive characteristics of steam and KOH activated carbons for supercapasitors, Journal of power sources. 144:302-309.Ionnidou, A and Zabaniotu. 2007. Agricultural residues of precursors for activated carbon production–a review, Renewable and sustainable energy reviews. 11:1705-1966.Kurniawan, F., Wongso, M., Ayucitra, A., Soetaredjo F.E., Angkawijaya A. E., Ju,Y. H., Ismadji, S. 2014. Carbon microsphere from water hyacinth for supercapacitor electrode. Journal of the Taiwan Institute of Chemical Engineers. 47: 197-201.Liu, B., Zhou, X., Chen, H., Liu, Y., Li, H. 2016. Promising porous carbons derived from lotus seedpods with outstanding supercapacitance performance. Electrochimica Acta. 208 :55–63.Taer, E., Mustika, W.S., Zulkifli, Syam, I.D.M., Taslim, R. Pengaruh Suhu Pengaktivan CO2 Terhadap Luas Permukaan Elektroda Karbon dan Sifat Kapasitan Sel Superkapasitor dari Kayu Karet. 2015. Prosiding Seminar Nasional Fisika Universitas Andalas (SNFUA). 96-100Taer, E., Taslim, R., Aini, Z., Hartati, S.D., Mustika, W.S. 2017. Activated carbon electrode from banana-peel waste for supercapacitor applications. AIP Conference Proceedings. 1801:040004-1-040004-4.Taer, E., Zulkifli., Arif, E.N., Taslim, R. Analisa Kapasitansi Spesifik Elektroda Karbon Superkapasitor dari Kayu Karet Terhadap Laju Scan Berdasarkan Variasi Aktivasi HNO3. 2016. Spektra Jurnal Fisika dan Aplikasinya. 1(1): 35-40.Yu, M., Han, Y., Li, J., Wang, L., 2016. CO2-activated porous carbon derived from cattail biomass for removal of malachite green dye and application as supercapacitors. Chemical Engineering Journal. 17:1-41.